PENGARUH PRAKTIK KERJA INDUSTRI, INFORMASI DUNIA KERJA DAN MOTIVASI KERJA TERHADAP KESIAPAN KERJA SISWA SMK NEGERI 1 SOPPENG - Nimatullah Muin; Hamsu Abdul Gani; Lu’mu (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
The study aims to examine the influence of industrial work practice, work information, and work motivation on students' work readiness. This study employed ex-post facto research method. The total population was 110 people and the samples of research were 84 people obtained by employing Proportional Random Sampling technique. Data collections used in this study were documentation and questionnaires. The prerequisite test used normality test, linearity test, multicollinearity test, and heteroscedasticity test. The results of the descriptive analysis reveal that: (1) the industrial work practice at SMKN 1 Soppeng is in high criteria, (2) the work information has high criteria, (3) the work motivation at SMKN 1 Soppeng has high criteria, and (4) the students' work readiness is in very ready category. The hypothesis testing employed simple linear regression and multiple linear regression. The results of the study indicate that: (1) there is an influence of industrial work practice on students’ work readiness at SMKN 1 Soppeng. The test result shows that the value of sig. of 0.002 < 0.05 with a contribution of 11%, (2) there is an influence of work information on students’ work readiness at SMKN 1 Soppeng. The test result shows that the value of sig. of 0.014 < 0.05 with acontribution of 7.2%, (3) there is an influence of work motivation on students’ work readiness at SMKN 1 Soppeng. The test result shows that the value of sig. of 0.015 < 0.05 with a contribution of 7%, and (4) there is an influence between industrial work practice, work information, and work motivation on work readiness of students at SMKN 1 Soppeng. The test result shows that the value of sig. of 0.007 <0.05 with a contribution of 14.1%. Therefore, the research hypothesis is accepted.